HISTOLOGICAL STUDY OF OVULAR ATRESTA “CORPUS LUTEUM” IN THE TELEOST PUNTIUS MUZAFFARPURENSIS (CYPRINIFORMES : CYPRINIDAE) - SHASHI, SHASHI. BHUSHAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1999)
The atretic condition of ova was common in the spawning stage and not in prespawning and immediately postspawning periods. Oocytes of any shaped and size took part in the formation of corpus luteum. The study of atretic ova of this fish revealed the deflection of oocytic membranes, disorganisation of nucleus and its disapperance, liquefaction of yolk. appearance of vacuoles in cytoplasm, proliferation of follicular cells, invasion of follicle cells into the cytoplasm and ultimately resorption of whole of the content of Ooplasm and appearance of yellow pigment in the follicular cells. Transformation of yolk granules into large yolk globules was also observed. Further, the dissolution of yolk globules and replacement of follicle cells in the yolk globules was also noticed.